Assessment of physical activity in older people with and without cognitive impairment - Hauer, Klaus; Lord, Stephen R.; Lindemann, Ulrich; Lamb, Sarah E.; Aminian, Kamiar; Schwenk, Michael (Journal of aging and physical activity, 2011)
The purpose of this study was to validate a new interview-administered physical activity questionnaire (Assessment of Physical Activity in Frail Older People; APAFOP) in older people with and without cognitive impairment. The authors assessed feasibility, validity, and test-retest reliability in 168 people (n = 78 with, n = 88 without cognitive impairment). Concurrent validity was assessed against an inertia-based motion sensor and an established questionnaire. Sensitivity to change was tested in an ongoing study in patients with mild to moderate dementia (n = 81). Assessment of physical activity by the APAFOP and the motion sensor correlated well in the total sample (TS; p = .705), as well as in the subsamples with cognitive impairment (CI; p = .585) and without CI (p = .787). Excellent feasibility with an acceptance rate of 100%, test-retest reliability (intraclass correlation coefficients ranging from .973 (TS) to .975 (CI) to .966 (no CI), and sensitivity to change (effect sizes: 0.35-1.47) were found in both subsamples.